Interactive multimedia as a tool to learn Bahasa Malaysia / Syuhaila Sabri - Sabri, Syuhaila (2017)
The use of Multimedia platform has been widely accepted as a useful and effective tool in learning second language. Many studies and researchers have examined the effectiveness of multimedia in learning second language from a number of aspects, including four skills of language learning: listening, speaking, reading and writing. Several researchers in Malaysia and the West concur that Bahasa Malaysia is a difficult language to master as a foreign language if they are not interested and lacking in confidence. This paper provides a brief overview of the effectiveness using multimedia platform in helping foreigner to learn Bahasa Malaysia. The use of multimedia platform in this study is to help foreigner learning Bahasa Malaysia in unique, short-cut method and interactive. The Malay language represented in these lessons is conversational Malay. The purpose of this study is to gain information about the Malaysian language to help foreigner learning Bahasa Malaysia step by step. The method used in this study is qualitative research whereby meta-analysis, empirical studies and ethnography approach has been used in conducting the research. The outcome of this study is an interactive mobile app as a storytelling system in helping foreigner to learn Bahasa Malaysia. Therefore, this study hopes that it will give benefit to the foreigner and tourist by helping them learning Bahasa Malaysia.